Role of fullerene electron transport layer on the morphology and optoelectronic properties of perovskite solar cells - Upama, M.; Elumalai, Naveen Kumar; Mahmud, M.; Wang, D.; Haque, F.; Gonçales, V.; Gooding, J.; Wright, M.; Xu, C.; Uddin, A. (2017)
High performance, hysteresis-free, low temperature n-i-p perovskite solar cells are successfully fabricated by solution processing using fullerene electron transport layer (ETL). PC71BM fullerene, with broader absorption spectrum and lower HOMO level, when incorporated in the perovskite solar cell yielded average power conversion efficiency (PCE) of 13.9%. This is the highest reported PCE in n-i-p perovskite solar cells with PC71BM ETL. The devices exhibited negligible hysteresis and high open-circuit voltage (Voc). On the contrary, devices with PC61BM, a common fullerene ETL in perovskite solar cell, exhibited large hysteresis and lower Voc. The underlying mechanisms of superior performance of devices with PC71BM ETL were found to be correlated with fullerene surface wettability and perovskite grain size. The influence of fullerene ETL on the perovskite grain growth and subsequent photovoltaic performance was investigated by contact angle measurement, morphological characterization of the surface topography and electrochemical impedance analysis.